2009
DOI: 10.1016/j.molcel.2009.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Differential SUMOylation of LXRα and LXRβ Mediates Transrepression of STAT1 Inflammatory Signaling in IFN-γ-Stimulated Brain Astrocytes

Abstract: To unravel the roles of LXRs in inflammation and immunity, we examined the function of LXRs in development of IFN-gamma-mediated inflammation using cultured rat brain astrocytes. LXR ligands inhibit neither STAT1 phosphorylation nor STAT1 translocation to the nucleus but, rather, inhibit STAT1 binding to promoters and the expression of IRF1, TNFalpha, and IL-6, downstream effectors of STAT1 action. Immunoprecipitation data revealed that LXRbeta formed a trimer with PIAS1-pSTAT1, whereas LXRalpha formed a trime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
102
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 37 publications
10
102
0
Order By: Relevance
“…Here, we demonstrated that LXR␣ was PARylated by PARP-1. Several post-translational modifications on LXR␣ have been previously described including phosphorylation (28), O-linked ␤-N-acetylglucosamine (O-GlcNAcylation) (55), acetylation (37), and sumoylation (56). These modifications on LXR␣ were shown to impact target gene expression through changes in LXR␣ stability, transactivation, and/or recruitment of transcriptional regulatory factors at specific target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that LXR␣ was PARylated by PARP-1. Several post-translational modifications on LXR␣ have been previously described including phosphorylation (28), O-linked ␤-N-acetylglucosamine (O-GlcNAcylation) (55), acetylation (37), and sumoylation (56). These modifications on LXR␣ were shown to impact target gene expression through changes in LXR␣ stability, transactivation, and/or recruitment of transcriptional regulatory factors at specific target genes.…”
Section: Discussionmentioning
confidence: 99%
“…RXR␣ as the obligate heterodimeric partner for FXR is also negatively regulated by SUMOylation (10). For example, there is recent evidence that SUMOylation of LXR␣ blocks the recruitment of RXR␣ to loci of LXR target genes (35)(36)(37). In addition to interference with interactions with coactivators, SUMOylation of NRs can also recruit corepressors such as RIP40 and the nuclear receptor corepressorhistone deacetylase (HDAC3) complex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to interference with interactions with coactivators, SUMOylation of NRs can also recruit corepressors such as RIP40 and the nuclear receptor corepressorhistone deacetylase (HDAC3) complex. Inhibition of corepressor release may also occur in a process called transrepression (4,36). Further studies will be required to define which of these or other mechanisms are operative in regulating the transcriptional activity of FXR.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR and LXR can further inhibit corepressor clearance from NF-B by preventing proteasomal degradation of NcoR1 in a ligand-and SUMOylation dependent manner [201,202]. SUMOylation is also implicated in LXRmediated transrepression of STAT1 downstream of interferon signaling [203]. Furthermore, PPAR interacts with both c-jun and p65 to repress AP-1-and NF-B-driven gene expression, respectively [204].…”
Section: Major Molecular Pathways In Inflammationmentioning
confidence: 99%